DISAIN DAN APLIKASI PENGATUR TEGANGAN AC SATU FASA - Effendi (Politeknik Aceh, 2019)
This single phase AC Voltage controller is arranged using such SCR TIC126, diodes, IC Regulators, Op-Amp LM324N, and several other electronic components.This module can produce AC voltages that vary according to the trigering of the SCR angle that is used, while the frequency of the output voltage waveform is fixed, the analysis of the output voltage waveform in this research is carried out in a simulation form by using the PSIM program, mathematically, and then comparing with the measurement results,as for the parameters measured is the Vrms output voltage. The voltage difference between simulated, mathematical and measurement is not too large,As for the triggering angle that used at of 45˚, 60˚, 90˚, 135˚, where the load used is resistive at 5 W 100 Ω, and the source that used is low AC voltage of 12.8 volts with a frequency of 50 Hz.